PERBANDINGAN PROFIL KANDUNGAN KIMIA EKSTRAK AIR, EKSTRAK HIDROTROPI, DAN EKSTRAK ETANOL RAMUAN JAMU SAINTIFIK PENURUN KADAR GULA DARAH SERTA UJI STABILITASNYA: CHEMICAL CONTENT PROFILE COMPARISON OF WATER EXTRACT, HYDROTROPIC EXTRACT, AND ETHANOLIC EXTRACT OF SCIENTIFIC JAMU FOR LOWERING BLOOD SUGAR LEVEL AND ITS STABILITY TEST - Sasmita, Sasmita; Retno Wahyuningrum; Ika Yuni Astuti (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
Scientific jamu for lowering blood sugar are used in the form of decoction preparations, so it is less practical. The method of using scientific herbal medicine which is still traditional has several disadvantages, namely it is impractical and reduces the level of patient compliance which can result in a decrease in the effectiveness of scientific jamu. Based on this, the development of scientific herbal medicine into a more modern dosage form is very important to do. The selection of the right extraction method and solvent will produce an extract with the most optimal active constituent in producing pharmacological effects, so that it can increase the effectiveness of research in the context of drug discovery and development. In this study, the chemical content profiles of 3 (three) different types of extracts were compared, namely water extract, hydrotropic extract, and ethanol extract. The three types of extracts were then compared for their yield values, total flavonoid levels, andrographolide, cinnamaldehyde, and curcumin. The total flavonoid levels were determined by the UV-Vis spectrophotometry method, the andrographolide, cinnamaldehyde, and curcumin levels were determined by the densitometry thin layer chromatography (TLC) method. The extract with the best chemical content profile was subjected to forced degradation tests. The results showed that the ethanol extract produced the highest yield compared to the water extract and hydrotrope extract, which was 4.48%. The ethanol extract also provided the best chemical content profile, namely the total flavonoid content of 16.15 ± 0.96 mg QE / g, andrographolide content of 2.14 ± 0.12%, cinnamaldehyde content of 8.22 ± 0.31%, and curcumin of 6.46 ± 0.80%. In the forced degradation test, the total flavonoid content in the ethanol extract decreased due to several conditions, such as hydrolysis, oxidation, thermal, and photolytic. Keywords: Extraction, Forced degradation, Hydrotropic, Scientific jamu